The Effect of Omega-3 on Mitigating Exercise-Induced Muscle Damage - Atiporn Therdyothin; Nacharin Phiphopthatsanee (My University, 2025)
Exercise-induced muscle damage (EIMD) refers to muscle injuries following exercises involving repetitive eccentric muscle contractions. The resultant inflammation and muscle protein leakage into the circulation lead to muscle pain and strength deficit, compromising athletic performance. This narrative review summarizes the current evidence on the effect and mechanism of omega-3 polyunsaturated fatty acids (n-3 PUFA) in potentially mitigating EIMD. Several studies suggested n-3 PUFA's role in alleviating delayed-onset muscle soreness, particularly in untrained individuals and those receiving higher doses of continuous supplementation. However, its impact on muscle strength attenuation and the reduction of performance post-exercise remains inconclusive. Also unclear are n-3 PUFA's effects on the reduction of circulating pro-inflammatory substances and muscle proteins. One of the possible mechanisms is its anti-inflammatory property, which involves its ability to incorporate into cell membranes and displace prostaglandin precursor. n-3 PUFA also decreases cyclooxygenase production and can be converted into specialized pro-resolving mediators (SPMs), further reducing inflammation. Moreover, n-3 PUFA's incorporation into cell membranes alters cell membrane properties, diminishing protein release during muscle breakdown. n-3 PUFA exhibits analgesic effects through SPM-induced modulation of receptors and ion channels, reducing both peripheral and central sensitization. n-3 PUFA also diminishes mitochondrial free radical production and accelerates nerve conduction, thereby improving voluntary muscle activation.
Keywords: Exercise and Physiological Responses